Assessment of the value of woodland landscape function to local communities in Gorongosa and Muanza districts, Sofala province, Mozambique - Lynam, T.; Cunliffe, R.; Mapaure, I.; Bwerinofa, I. (Center for International Forestry Research, 2003)
This book is a report of a short-term research project. The project aimed to test an approach for estimating local values for landscape units and relate these to formal biodiversity conservation values in Gorongosa National Park (GNP), Sofala Province, Mozambique. First section describes the research site selection and gives short descriptions of the chosen sites: Muaredzi and Nhanchururu. Second section is about the community landscape valuations, includes also the methods and results concerning conceptual models, spatial data sets, and participatory community assessments. Vegetations inventory and generation of biodiversity conservation values are explained in third section. Section four explains the community and biodiversity conservation valuations. The last chapter synthesizes the various results together and describes the findings in terms of the land use planning process in terms of community and biodiversity evaluations.